Towards Healthy and Sustainable Human Settlement: Understanding How Local Communities Perceive and Engage with Spa Tourism Development Initiatives in Rural Areas - Maja Mijatov Ladičorbić; Aleksandra S. Dragin; Tamara Surla; Aleksandra Tešin; Juan Manuel Amezcua-Ogáyar; Alberto Calahorro-López; Vladimir Stojanović; Zrinka Zadel; Kristina Košić; Olja Munitlak Ivanović; Anđelija Ivkov Džigurski; Miroslav D. Vujičić; et al. (Land)
This study investigated the intersection of healthy and sustainable human settlement, and land use for spa tourism in rural areas. Recognizing the crucial role of youth in shaping the future of tourism, this research aimed to provide an insight into the young local rural community representatives’ perception of sustainable spa tourism development and to identify whether these attitudes are shaped by their socio-demographic characteristics. The applied methodology was the Sustainable Tourism Attitude Scale (SUS-TAS). A total of 254 respondents took part in this research. Using SPSS 30.0.0, the gathered data were subjected to additional analyses based on factor analysis, descriptive statistics, and the general linear model. The results showed a general positive attitude of local community members towards the further development of spa tourism in their communities. The especially important factors were the following: long-term planning of development, environmental protection, negative attitudes towards spa tourism development, economic benefits, as well as community participation. By providing an empirical analysis based on the use of robust tools for measuring youth attitudes, this research offers valuable insights for policymakers, planners, and community leaders into how they can design and implement tourism strategies that align with sustainability principles while fostering local economic development and environmental stewardship. The ultimate goal is to contribute to the broader discussion on developing healthy, sustainable human settlements that balance economic benefits with ecological and social well-being. Synergy/harmony between communities and their natural surroundings is essential for the social, economic, and environmental sustainability of rural human settlements. Mineral springs and spas facilitate sensory experiences for individuals (both tourists and residents) through the utilization of natural resources and the environment.